Literatura e ensino: alteridades e interseccionalidades na formação do leitor de textos literários - Silva , Josiane de Almeida (2022)
In this research, we discuss the importance of the teacher's mediating role in the teaching and learning of literature, in the sense of contributing to the formation of student readers with a view to entertainment, aesthetic enjoyment, human sensitivity and the construction of autonomy and dignity in the exercise of citizenship. We consider that literature, in its main objective, should provide an understanding of the effective role of alterity in the interaction of people, the formation of readers, cultural diversity, gender, language, race, that is, the intersectionalities inherent to the human being, such as aspects related to literature and to teaching. Specifically, we conceived the proposal for the legal implementation of literary education and literary literacy. In this sense, the theoretical contribution of the study highlights the dialogical conception of language (BAKHTIN, 2009 [1929]); the transformations related to reading and literature in Brazilian society (ARANA; KLEBIS, 2015); the humanizing and sensitive power of literature (CANDIDO, 1972), literary literacy (COSSON, 2006), in addition to Perrone-Moisés (2006), Zilberman (1989), Cosson (2006), Silva (2004) among other authors and approaches related to the theme. Methodologically, we present a bibliographic- documentary, highlighting official documents such as the National Curricular Parameters (PCN), the Curriculum Guidelines for High School (OCNEM) and the National Curricular Common Base (BNCC), for the work of literary education in basic education, aiming to gather sufficient information about teaching practice, in accordance with what is proposed, above all, in the national curriculum guidelines of teaching, in order to guarantee effectiveness in the reading of the literary text and in the formation of sensitive, critical and reflective readers. From the conclusions, we highlight the progressive erasure of Literature and the alleged invisibility of certain aspects that lead to the continuity or intensification of problems in this area (MENDES, 2020), as an important curricular component for an education that has as its essential focus the formation of readers of aesthetic texts, in their different forms of literary manifestation. Denying Literature is to distance students from reading different literary genres that demonstrate human diversity in its cultural, historical, political, and social plurality, since literary texts represent a set of knowledge (IPIRANGA, 2019) experienced by man throughout its history, and (re)signified by language.